Examining Chinese Minority Education Policies - Yan, Qiyuan (Transactions on Social Science, Education and Humanities Research, 2024)
China is renowned for its rich cultural tapestry, diverse ethnic groups, and complex history. While Han Chinese make up the majority of the population, China is also home to a mosaic of 55 ethnic minorities, each with its unique customs, languages, and traditions. While they may share some similarities, each minority ethnic group has their own unique culture and language that differs from other groups and sometimes their differences have caused conflict between each other. Therefore, when writing and implementing policy for minority education, it is important to be adaptable and flexible to local conditions. The Chinese government has increasingly emphasized minority education as an important factor for social unity. In late 20th century, Premier Zhou Enlai decided to create written language for minority groups such as the Hani and Bai, while in 2020, Chairman Xi decided to shift promotion to protection by creating an online archive for minority languages and cultures such as folklore and the creation myth. This paper critically examines the effectiveness of China’s bilingual education policy, teacher training initiatives, and the mechanisms of two exemptions and one subsidy for minority education in compulsory education schools in Yunnan. The study underscores the laudable intentions behind these policies while shedding light on the numerous challenges encountered during their implementation.